VARIASI MORFOLOGI JENIS INANG Subulura andersoni Cobblod, 1887 DI INDONESIA DAN DESKRIPSI Subulura sipiroki n.sp. - Purwaningsih, Endang (Research Center for Biology-Indonesian Institute of Sciences, 2003)
Subulura andersoni (Nematoda:Â Subuluroidae) recovered from some of Muridae in several places in Indonesia was observed for morphological variation. There kinds of tail morphology were found e.g tail with short and bluntly rounded spike, tail with longer and sharply pointed spike, and tail with antero ventrally curve spike, The new species ofÂ Subulura sipiroki n.sp. recovered from Leopoldamys sabanus in Sumatera also described.